2008 SC - International Conference for High Performance Computing, Networking, Storage and Analysis 2008
DOI: 10.1109/sc.2008.5213939
|View full text |Cite
|
Sign up to set email alerts
|

BitDew: A programmable environment for large-scale data management and distribution

Abstract: Abstract:Desktop Grids use the computing, network and storage resources from idle desktop PC's distributed over multiple-LAN's or the Internet to compute a large variety of resource-demanding distributed applications. While these applications need to access, compute, store and circulate large volumes of data, little attention has been paid to data management in such large-scale, dynamic, heterogeneous, volatile and highly distributed Grids. In most cases, data management relies on ad-hoc solutions, and providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…BitDew [7] is a middleware that exploits protocols like P2P, http, BitTorrent and ftp, and selects the best protocol depending on data size. BitDew architecture is decentralized and has independent services for Data Scheduler, Data Catalog, Data Repository and Data Transfer.…”
Section: Bitdew-mapreducementioning
confidence: 99%
See 2 more Smart Citations
“…BitDew [7] is a middleware that exploits protocols like P2P, http, BitTorrent and ftp, and selects the best protocol depending on data size. BitDew architecture is decentralized and has independent services for Data Scheduler, Data Catalog, Data Repository and Data Transfer.…”
Section: Bitdew-mapreducementioning
confidence: 99%
“…BitDew [7] is a middleware for large scale data management on hybid distributed computing infrastructures. Its runtime environment supports the use of multiple file transfer protocols: either client/server (http, ftp, scp), P2P (bittorrent), Grid (through the SAGA API) or Cloud (Amazon S3, Dropbox).…”
Section: B Bitdew-mapreduce Simulation Modulementioning
confidence: 99%
See 1 more Smart Citation
“…This approach complements Grid'5000 where the experimental conditions are controlled and reproducible but far from real life Internet condition. BitDew [8] is a middleware dedicated to data management on Desktop Grid. In addition with traditional microbenchmarks performed on Grid'5000, several real-life scenarios have been run on DSL-Lab.…”
Section: Evaluation Of Desktop Grid Platformsmentioning
confidence: 99%
“…The experiments on the DSL-Lab platform have shown that the BitDew middleware was able to cope with complex scenarios in situations close to real-world deployment. We report on two scenarios that were previously published in [8] to illustrate the specificity of DSL-Lab with respect to quantitative performance evaluation.…”
Section: Evaluation Of Desktop Grid Platformsmentioning
confidence: 99%